Immunoresponse of Coho salmon immunized with a gene expression library from Piscirickettsia salmonis - MIQUEL,ALVARO (Sociedad de Biología de Chile, 2003)
We have used the expression library immunization technology to study the protection of Coho salmon Oncorhynchus kisutch to the infection with Piscirickettsia salmonis. Purified DNA from this bacterium was sonicated and the fragments were cloned in the expression vector pCMV-Bios. Two libraries were obtained containing 22,000 and 28,000 colonies and corresponding to approximately 8 and 10 times the genome of the pathogen, respectively. On average, the size of the inserts ranged between 300 and 1,000 bp. The plasmid DNA isolated from one of these libraries was purified and 20 µg were injected intramuscularly into 60 fish followed by a second dose of 10 µg applied 40 days later. As control, fish were injected with the same amount of DNA of the vector pCMV-Bios without insert. The titer of IgM anti-P. salmonis of vaccinated fish, evaluated 60 days post-injection, was significantly higher than that of the control group injected with the vector alone. Moreover, this response was specific against P. salmonis antigens, since no cross reaction was detected with Renibacterium salmoninarum and Yersinia ruckeri. The vaccinated and control fish were challenged 60 days after the second dose of DNA with 2.5 x 10(7) P. salmonis corresponding to 7.5 times the LD50. At 30 days post-challenge, 100% mortality was obtained with the control fish while 20% of the vaccinated animals survived. All surviving fish exhibited a lower bacterial load in the kidney than control fish. The expression library was also tested in Balb/c mice and it was found that the humoral immune response was specific to P. salmonis and it was dependent on the amount of DNA injected